Engaging virtual agents - Iurgel, Ido A. (2013)
Embodied virtual assistants normally don’t engage the user emotionally. They fulfil their functions, e.g. as shopping assistants or virtual teachers, factually and emotionless. This way, they do not explore the full potential of the presence of an embodied character. In real life, the personality of the teacher or salesperson, their ability to involve and even to entertain is essential for their success. But how much of these “soft factors” can be translated into behaviour of virtual agents? Which kinds of virtual personalities are appropriate for which group, and in which context? We call virtual agents with engaging “soft skills” Engaging Virtual Agents. This paper presents a software platform employed for experimenting with soft skills and for creating different personalities of virtual agents. The focus of this platform is on authoring principles that facilitate the cooperation of content creators and computer scientists. We also present “Julie”, an example that was shortly concluded as part of a research project commissioned by SAP AG. Julie is a virtual sales assistant that employs actively emotional expressions and narrative techniques, in order to provide additional motivation for the customer to visit and to remain at the virtual shop.